Launching reverse-innovated product from emerging markets to MNC's home market: A theoretical framework for MNC's decisions. Issue 1 (February 2017) - Zhu, Fengxia; Zou, Shaoming; Xu, Hui
Highlights: A framework is developed for linking product characteristics to a MNC's decision to launch a reverse-innovated product to its home market. Perceived degree of needed product adaptation and perceived risk of cannibalization are the important mechanisms through which product characteristics impact MNC's reverse launch decision. Market competitive intensity and MNC's global orientation moderate the effects of these two mechanisms on MNC's reverse launch decision. Abstract: A reverse-innovated product is a new product that is originally developed for an emerging market by MNCs. The increasing number of MNCs engaging in reverse innovation and the criticality of new products to an MNC's performance and competitive advantage make reverse innovation an important area for academic research and managerial practices. This paper integrates relevant literature and proposes a theoretical framework to understand the mechanisms by which the characteristics of a reverse-innovated product affect management's decision to launch that product in a developed market (e.g., the MNC's home market). By means of literature review, the paper identifies two underlying evaluation mechanisms through which the reverse-innovated product characteristics are linked to management's reverse launch decision: the perceived degree of needed adaptation and the perceived risk of cannibalization. The authors also derive several propositions for future empirical research and discuss implications for future research.